Medialny wymiar legitymizacji władzy - Secler, Bartłomiej (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2012)
The issue of the legitimization of political power is one of the essential research issues of political science. Legitimization is usually defined as the entitlement of the authorities to make legal decisions accepted by the governed. The author of the paper discusses the issue of relations between the authorities and the media emphasizing the media character (dimension) of the process of legitimization of power. The attempt to approach the issue in this manner is justifiable since the contemporary media constitute a significant link in the relations between the governing and the governed. What is more, the media influence political processes in a state, shape citizens’ attitudes to politics and authorities, and the freedom of the media is perceived as providing one of the foundations of democracy. The media are sometimes named ‘the fourth estate’. Depending on the political system, the media can facilitate winning (or maintaining) power by a political elite, or legitimize power that has been forcefully imposed (in non-democratic systems). The basic goal of the paper is to reflect on the role and significance of the mass media in the process of legitimization of power.